Differentiation of meat quality, lipid oxidation and fatty acid profile between Cobb 500 breed and Sasso breed - Norazman, Muhammad Syukur (2015)
The aim of the experiment was to study the differences in meat quality, lipid oxidation and fatty acids between Cobb 500 breed and Sasso breed chicken.The experiment involve total of 30 roosters (n = 15 of Sasso breed and n = 15 of Cobb 500 breed ). They were separated by breed in litter floor space management and all birds were fed with commercial diet. Cobb 500 breed was slaughtered at the age of 42 days, while Sasso breed was slaughtered at the age of 56 days. Meat sample was stored at 4℃ for 24 hours after slaughtered. Meat quality assessment ( ultimate pH , drip loss, cooking loss, colour) and lipid oxidation were conducted on the breast ( pectoralis muscle ) while fatty acid profile were conducted on both breast and thigh muscles (femorocruralis muscle ). Cobb 500 breed had higher ( P< 0.05 ) lightness value (L*) and higher ( P> 0.05 ) cooking loss compared to Sasso breed. Malanonaldehyde (MDA) value at day 7 was lower ( P> 0.05 ) in Cobb 500 breed compare Sasso breed. Sasso breed muscles contained more saturated fatty acids than Cobb 500 breed muscles. Sasso breed showed a higher percentage of polyunsaturated fatty acids ( P < 0.05) and a lower percentage of monounsaturated fatty acids (P< 0.05) than Cobb 500 breed chicken muscles. In conclusion, pH , L* values and cooking loss was higher for Cobb 500 breed compared to Sasso breed. Cobb 500 breed MDA value was lower than Sasso breed. Sasso chicken meat contained higher omega-3 polyunsaturated fatty acids (PUFA) than Cobb 500 breed. Hence, Sasso breed had better nutritional values in terms of fatty acid profile. However, Sasso breed meat had shorter shelf life compared with Cobb 500.